A population‐based analysis of Head and Neck hemangiopericytoma. (5th October 2015) - Shaigany, Kevin; Fang, Christina H.; Patel, Tapan D.; Park, Richard Chan; Baredes, Soly; Eloy, Jean Anderson
Abstract : Objectives/Hypothesis: Hemangiopericytomas (HPC) are tumors that arise from pericytes. Hemangiopericytomas of the head and neck are rare and occur both extracranially and intracranially. This study analyzes the demographic, clinicopathologic, treatment modalities, and survival characteristics of extracranial head and neck hemangiopericytomas (HN‐HPC) and compares them to HPCs at other body sites (Other‐HPC). Methods: The Surveillance, Epidemiology, and End Results (SEER) database (1973–2012) was queried for HN‐HPC (121 cases) and Other‐HPC (510 cases). Data were analyzed comparatively with respect to various demographic and clinicopathologic factors. Disease‐specific survival (DSS) was analyzed using the Kaplan‐Meier model. Results: There was no significant difference in age at time of diagnosis between HN‐HPC and Other‐HPC. Head and neck HPC was most commonly located in the connective and soft tissue (18.4%), followed by the nasal cavity and paranasal sinuses (8.5%). Head and neck HPCs were smaller than Other‐HPC ( P  < 0.0001) and more likely to be a lower histologic grade ( P  < 0.0097). The primary treatment modality for HN‐HPC was surgery alone, used in 55.8% of cases. The 5‐, 10‐, and 20‐year DSS for HN‐HPC were 84.0%, 79.4%, and 69.4%, respectfully. Higher histologic grade and the presence of distant metastases were poor prognostic factors for HN‐HPC. Conclusion: Head and neck HPCs are rare tumors. This study represents the largest series of HN‐HPCs to date. Surgery alone is the primary treatment modality for HN‐HPC, with a favorable prognosis. Adjuvant radiotherapy does not appear to confer a survival benefit for any body site. Level of Evidence: 4. Laryngoscope, 126:643–650, 2016